2023
DOI: 10.1038/s41598-023-35362-7
|View full text |Cite
|
Sign up to set email alerts
|

Phase II trial of delta-tocotrienol in neoadjuvant breast cancer with evaluation of treatment response using ctDNA

Abstract: Neoadjuvant treatment of breast cancer is applied to an increasing extent, but treatment response varies and side effects pose a challenge. The vitamin E isoform delta-tocotrienol might enhance the efficacy of chemotherapy and reduce the risk of side effects. The aim of this study was to investigate the clinical effect of delta-tocotrienol combined with standard neoadjuvant treatment and the possible association between detectable circulating tumor DNA (ctDNA) during and after neoadjuvant treatment with pathol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…40 Previous evidence suggests that ZNF296 is an effective biomarker for breast cancer detection. 41 Furthermore, recent studies have found that ZNF296 is a regulator of H3K9me3 and is closely associated with the pluripotency of embryonic stem cells. 42 Another study indicated that ZNF296 was associated with the formation of induced pluripotent stem (iPS) cells.…”
Section: Discussionmentioning
confidence: 99%
“…40 Previous evidence suggests that ZNF296 is an effective biomarker for breast cancer detection. 41 Furthermore, recent studies have found that ZNF296 is a regulator of H3K9me3 and is closely associated with the pluripotency of embryonic stem cells. 42 Another study indicated that ZNF296 was associated with the formation of induced pluripotent stem (iPS) cells.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Kjaer et al. [ 152 ] reported that δTE at 300 mg thrice a day did not enhance the efficacy of neoadjuvant breast cancer treatment or reduce the frequency of side effects in a phase II trial involving 80 patients with newly diagnosed breast cancer (NCT02909751). On the contrary, δTE at daily 400–1600 mg induced apoptosis in dysplastic or malignant pancreatic tissues in a phase I trial including 25 patients for curative surgical resection with presumptive premalignant or malignant neoplasms of exocrine pancreas (NCT00985777) [ 25 ].…”
Section: The Effects Of γT-rich Tocopherols On Pca and Tes On Other T...mentioning
confidence: 99%